The Role of Chromatin Remodeling Complexes in Gene Expression and Genome Stability - Israa Jasim Alswaili (American Journal of Biology and Natural Sciences, 2024)
Chromatin remodeling complexes are involved in the process of the redox state of chromatin and cell differentiation as well as in cellular processes, such as DNA repair, replication and transcription. This work attempts to establish the roles of chromatin remodeling complexes more particularly, gene regulation and genome stability. By employing RNA-Seq, comet assays, γH2AX foci formation assays, and GFP-based HR and NHEJ efficiency assays we assessed the effects of chromatin remodeler deficiencies. Therefore, using RNA-Seq, the authors found that there were alterations at the transcriptional level as well as increased DNA damage evaluated with comet and γH2AX assays. Furthermore, it was observed that efficiency of both HR and NHEJ are decreased in chromatin remodeler knocked-down cells. Therefore, the results of our study give the detailed picture of the involvement of chromatin remodeling complexes in various processes and emphasizes their importance for the understanding of the pathogenesis of the diseases which are accompanied by the alterations in the activity of chromatin remodeling complexes and their further treatment.